Improving English Learning Outcomes Through Problem Based Learning (PBL) Models in Class VII Students of SMP Negeri 9 Kendari - Marfiah (Persatuan Guru Republik Indonesia Provinsi sulawesi Tenggara, 2023)
This study aims to find a learning model to improve English learning outcomes in class VII students of SMPN 9 Kendari through problem-based learning. This research was carried out in the odd semester of the 2022/2023 school year at SMPN 9 Kendari for class VII-4 students, totaling 37 students. The factors observed in this study are student factors and teacher factors. This research was carried out in 2 (two) cycles, including a) planning; b) implementation of actions; c) observation and evaluation, and d) reflection. The data obtained in this study were analyzed quantitatively and qualitatively. The results showed: (1) student test scores for each action continued to increase after reflecting on each action. It is known that the average in the first cycle of action is 70.14 and in the second cycle 83.11, (2) student learning outcomes after using the problem-based learning model by doing reflection and the average student learning outcomes increases. This increase increased in cycle II by 89.9% from cycle I, which amounted to 43.24%.